Technologies Using Interactive Methods in Developing Creative Skills of Preschool Children - Usmanova Saodat Erkinovna (Zien Journals, 2023)
This article discusses the role of innovative methods and modern technologies in the development of children's creative abilities in preschool educational institutions.
Keywords: material and technical base; information communication; theater performances